2001
DOI: 10.1099/00207713-51-2-547
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Ralstonia pickettii biovar 3/'thomasii' strains (Pickett 1994) and of new isolates related to nosocomial recurrent meningitis as Ralstonia mannitolytica sp. nov.

Abstract: Classification of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 37 publications
3
78
1
3
Order By: Relevance
“…Reactions in the API20NE system (bioMérieux) were positive for gluconate (n ϭ 5), caprate (n ϭ 5), and malate (n ϭ 5) and were variable for adipate (n ϭ 3) and citrate (n ϭ 1). This biochemical profile was consistent with an identification as R. gilardii (2,3). It should be mentioned that all strains were found to have multiperitrichous flagella instead of a single polar flagellum as described previously (2).…”
supporting
confidence: 68%
“…Reactions in the API20NE system (bioMérieux) were positive for gluconate (n ϭ 5), caprate (n ϭ 5), and malate (n ϭ 5) and were variable for adipate (n ϭ 3) and citrate (n ϭ 1). This biochemical profile was consistent with an identification as R. gilardii (2,3). It should be mentioned that all strains were found to have multiperitrichous flagella instead of a single polar flagellum as described previously (2).…”
supporting
confidence: 68%
“…The R. insidiosa strains used in this study, several of which have been deposited in the culture collections of the BCCM/LMG (Laboratorium voor Microbiologie Gent, Belgium) and CCUG (University of Göteborg, Department of Clinical Bacteriology, Göteborg, Sweden), are listed in Table 1. Type and reference strains of all other Ralstonia species have been described previously Vandamme et al, 1999;Chen et al, 2001;De Baere et al, 2001;Goris et al, 2001). Strains were grown aerobically on Mueller-Hinton broth (Becton Dickinson) supplemented with 1?8 % (w/v) agar and incubated for 24 h at 32 uC, unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Ralstonia pickettii has been isolated from various clinical sources (Riley & Weaver, 1975;McNeil et al, 1985) and has been found to be responsible for pseudobacteraemia (Verschraegen et al, 1985). Strains of R. mannitolilytica (formerly known as 'Pseudomonas thomasii' and R. pickettii biovar 3) have also been isolated from various clinical sources, including nosocomial recurrent meningitis (Philips et al, 1972;De Baere et al, 2001;Vaneechoutte et al, 2001). R. gilardii, R. paucula and R. taiwanensis have been isolated both from human clinical samples and from the environment Vandamme et al, 1999;Chen et al, 2001;Wauters et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…5). These peptides are from the enzyme toluene-3-monooxygenase of the two very closely related bacteria strains Burkolderia cepacia and Ralstonia pickettii [25][26][27][28]. Both bacteria are ubiquitous in the environment but rarely cause symptomatic infection in healthy individuals [29].…”
Section: S a R W N T P T A M32253mentioning
confidence: 99%